How does alcohol use impact morbidity and mortality of liver cirrhosis?: A systematic review and dose-response meta-analysis - Llamosas-Falcón, Laura; Probst, Charlotte; Buckley, Charlotte; Jiang, Huan; Lasserre, Aurélie M.; Puka, Klajdi; Tran, Alexander; Zhu, Yachen; Rehm, Jürgen (Hepatology international, 2024)
Background  Alcohol consumption is the most important risk factor responsible for the disease burden of liver cirrhosis (LC). Estimates of risk relationships available usually neither distinguish between different causes such as alcohol-related LC or hepatitis-related LC, nor differentiate between morbidity and mortality as outcome. We aimed to address this research gap and identify dose-response relationships between alcohol consumption and LC, by cause and outcome. - Methods  A systematic review using PubMed/Medline and Embase was conducted, identifying studies that reported an association between level of alcohol use and LC. Meta-regression models were used to estimate the dose-response relationships and control for heterogeneity. - Results  Totally, 44 studies, and 1 secondary data source, with a total of 5,122,534 participants and 15,150 cases were included. Non-linear dose-response relationships were identified, attenuated for higher levels of consumption. For morbidity, drinking 25 g/day was associated with a RR of 1.81 (95% CI 1.68-1.94) compared to lifetime abstention; 50 g/day and 100 g/ day corresponded to 3.54 (95% CI 3.29-3.81) and 8.15 (95% CI 7.46-8.91), respectively. For mortality, for 25 g/day, a RR of 2.65 (95% CI 2.22-3.16); for 50 g/day, a RR of 6.83 (95% CI 5.84-7.97); for 100 g/day, a RR of 16.38 (95% CI 13.81-19.42) were identified. A higher risk for alcohol-related and all-cause LC as compared to hepatitis C-related LC was found. - Conclusion  Our results demonstrated higher acceleration for mortality compared to morbidity. The current findings will inform the way we quantify the burden due to LC attributable to alcohol use.